Synthesis of Novel Hybrid Lonidamine-Coumarin Derivatives and Their Anticancer Activities - Ipek, Ozgecan Savlug; Sucu, Bilgesu Onur; Gul, Seref; Yolacan, Cigdem; Guzel, Mustafa (ELSEVIER, 2023)
In order to develop drugs against cancer, which is one of the deadliest diseases in the world, hybridiz-ing structures with known anticancer activity can provide a dual activity for the treatment of cancer cases. For this purpose, a series of novel hybrid compounds combining lonidamine and 7-hydroxy-4-methylcoumarin via different linker modifications have been synthesized in this study. The chemical structures of the novel compound were elucidated with 1 H and 13 C NMR and mass spectrometry (HRMS) methods. All the synthesized compounds were screened for anticancer activity against MCF-7 and A549 cells. Among them, compound 2 appeared to be the most potent compound on MCF-7 lines; and IC50 dose was determined as 33.12 mu M. IC50 of Compound 6 was determined as 139.6 mu M for A549 cells. Con-sidering anticancer activity studies, compounds 2 and 6 have potential to lead to the development of novel hybrid compounds for cancer therapy. Further studies to identify mechanistic explanations of the bioactivity of these molecules are ongoing and will be reported in due course.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Lonidamine; Coumarin; Anti -cancer activity; Drug discovery; CANCER-CELL-METABOLISM; SCHIFF-BASES; DESIGN; 7-HYDROXYCOUMARIN; XENOGRAFTS; MECHANISM; DISCOVERY; PROSTATE; ANALOGS; POTENT; Chemistry